Calibrated rare variant genetic risk scores for complex disease prediction using large exome sequence repositories - Ricky Lali; Michael Chong; Arghavan Omidi; Pedrum Mohammadi-Shemirani; Ann Le; Edward Cui; Guillaume Paré (Nature Communications, 2021)
Identifying associations of rare variants with disease is challenging due to small effect sizes, technical artefacts and population structure heterogeneity. Here, the authors present RV-EXCALIBER, a method that uses large summary-level exome data to robustly calibrate rare variant burden.